Comprehensive Analysis of G-Quadruplexes in African Swine Fever Virus Genome Reveals Potential Antiviral Targets by G-Quadruplex Stabilizers - Muturi, Elishiba; Meng, Fei; Liu, Huan; Jiang, Mengwei; Wei, Hongping; Yang, Hang (Frontiers in Microbiology, 2021)
ASFV, a lethal hemorrhagic fever of the swine, poses a major threat to the world's swine population and has so far resulted in devastating socio-economic consequences. The situation is further compounded by the lack of an approved vaccine or antiviral drug. Herein, we investigated a novel anti-ASFV approach by targeting G-quadruplex (G4) in the viral genome. Bioinformatics analysis of putative G-quadruplex-forming sequence (PQS) in the genome of ASFV BA71V strain revealed 317 PQSs on the forward strand and 322 PQSs on the reverse strand of the viral genome, translating to a density of 3.82 PQS/kb covering 9.52% of the entire genome, which means that 85% of genes in the ASFV genome have at least 1 PQS on either strand. Biochemical characterization showed that 8 out of 13 conserved PQSs could form stable G4s in the presence of K+, and 4 of them could be stabilized by G4 ligands, NMM, and PDS in vitro. An EGFP-based reporting system revealed that the expression of two G4-containing genes, i.e., P1192R and D117L, could be significantly depressed by NMM and PDS in 293T cells. In addition, a virus infection model showed that NMM inhibits the replication of ASFV in PAM cells with an EC50 value of 1.16 µM. Altogether, the present study showed that functional PQSs existent in the promoters, CDS, 3' and 5' UTRs of the ASFV genome could be stabilized by G4 ligands, such as NMM and PDS, and could serve as potential targets for antivirals.